Therapy Play sebagai Upaya Trauma Healing oleh Komunitas Kejar Mimpi Cianjur pada Penyintas Anak-anak Bencana Bumi Cianjur 2022 - Lia Maliadani; Wa Ode Asmawati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
In November 2022, Cianjur experienced an earthquake with a magnitude of 5.6 on the SR, which was followed by several aftershocks. As a result, the people of Cianjur experienced material and non-material losses such as houses being damaged or even collapsed, the loss of family members, or post-disaster trauma, especially for children. One of the communities working to help survivors is KM Cianjur, which focuses on trauma healing activities for children. This research uses descriptive-qualitative methods by collecting data through interviews and documentation. The total research population was 380 children in 4 villages, and the research subjects used random sampling techniques, namely 100 children in Kp Cirumput. The results of this research are trauma healing carried out by the KM Cianjur community using play therapy such as fun games, singing, and games with elements of knowledge. As a result of trauma healing, there are positive changes in children, as evidenced by the return of their functioning and their lifestyles starting to improve.